A reconfiguração do mandato político endereçado à educação superior Europeia - António Manuel Magalhães (EccoS – Revista Científica)
This article analyses the educational implications that the political, economic and social policies of the last decades have been promoting in European higher education. The analysis of the dissolution of modern narrative of the university and higher education supports the argument that, in the context of the development of the European Higher Education Area, the mandate addressed to higher education is being reconfigured by the articulations between 'education' research 'and' innovation promoted by the 'knowledge triangle' disseminated by the European Union . Based on the analysis of these articulations in the texts endorsed by the European ministers in the framework of the Bologna process, it is argued that, under hegemony of innovation, the productivist mandate addressed to European higher education is legitimised. The article proposes that greater centrality in the field of educational research is given to the impacts that the transformations politically induced in European higher education potentially (and already de facto) have on its educational concepts and practices.